Survival Rate of Sand Goby, Oxyeleotris marmorata (Blkr.), Fed by Carrot-Enriched Rotifers, Brack ion us sp. - Irzal Effendi; Dedi Jusadi; A.I. Nirwana (Indonesian Society of Scientific Aquaculture (ISSA), 2004)
The aim of this experiment is to know survival rate of sand goby larvae were fed carrot-enriched rotifers. Two days old larvae (3,56-3,57 mm body length) were reared in conical fiberglass tanks filled 100 1 of water with stocking density 23 fish per 1 (2.300 fish per tank). The tanks were placed in transparent-roofed room and the water was aerated softly by 3 unit of aeration stones. Larvae were fed carrot-enriched rotifers and without enrichment as a control. Stocking density of rotifers was 40 individual per ml or 4x106 individual per tank and it maintained for 10 days of rearing. Rotifers were incubated in media which contained (60 g per 1) sieved carrot (100 urn) for 2,5 hours before fed to the larvae. The survival rate of sand goby larvae, which fed by carrot-enriched rotifers (29,9%), was higher (p